A Normative Brain MRI Database of Neurotypical Participants from 5 to 90 Years of Age. (3rd March 2023) - Treit, Sarah; Rickard, Julia N.; Stolz, Emily; Solar, Kevin; Seres, Peter; Emery, Derek; Beaulieu, Christian
ABSTRACT: Brain magnetic resonance imaging (MRI) studies of clinical populations often require comparison to a normative 'control' cohort, usually of similar age/sex, scanned with the same protocol. The goal here was to create a normative brain MRI database of common quantitative methods to be used in comparisons with a variety of neurological disorders across the lifespan. 378 neurotypical controls (aged 5–90 years; median 31 years; 216 females, 162 males) completed brain MRI, cognitive testing, clinical assessment, and a demographics questionnaire. In addition, this large normative sample will yield novel insight into healthy brain development and aging.